2014
DOI: 10.1007/s13277-014-2921-x
|View full text |Cite
|
Sign up to set email alerts
|

Polygala tenuifolia polysaccharide PTP induced apoptosis in ovarian cancer cells via a mitochondrial pathway

Abstract: One purified polysaccharide protein tyrosine phosphatase (PTP) was isolated from the roots of Polygala tenuifolia. The aim of the present study is to investigate the antitumor effect of PTP on human ovarian cancer OVCAR-3 cells and explore the molecular mechanism of the action involved. The results of MTT assay and apoptosis detection assay showed that PTP inhibited cellular proliferation of OVCAR-3 cells and induced apoptotic cellular death via arresting cell circle at the G0/G1 phase. Reverse transcription-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Immune-enhancing effects have been demonstrated to occur with AbM, including anti-oxidant, anti-mutagenic and anti-tumor effects ( 32 ). The positive mechanism of action of various medicinal plants in acute myeloid leukemia occurs via polysaccharides, which is primarily associated with; inhibition of cell proliferation, invasion and further induction of cancer cell apoptosis ( 33 ). Apoptosis is a form of programmed cell death without the accompanied inflammation, a phenomenon that has been a popular topic in anti-cancer research ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immune-enhancing effects have been demonstrated to occur with AbM, including anti-oxidant, anti-mutagenic and anti-tumor effects ( 32 ). The positive mechanism of action of various medicinal plants in acute myeloid leukemia occurs via polysaccharides, which is primarily associated with; inhibition of cell proliferation, invasion and further induction of cancer cell apoptosis ( 33 ). Apoptosis is a form of programmed cell death without the accompanied inflammation, a phenomenon that has been a popular topic in anti-cancer research ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of polysaccharides from various medicinal plants has been demonstrated in ovarian cancer cells, which is mostly associated with the inhibition of cell proliferation, migration and invasion, and the induction of cell apoptosis [ 28 , 29 ]. Se has also been found to play a role in prevention and treatment of ovarian cancer [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. tenuifolia is the most dominant origin plant of Polygalae Radix [ 16 ], and is an ingredient in numerous medicines and prescriptions in East Asia [ 17 ]. Based on laboratory studies and clinical practice, P. tenuifolia possesses various biological and therapeutic actions and functions as a mucolytic, tonic, sedative, antipsychotic, and expectorant [ 14 , 18 , 19 ]. Phytochemical studies of the dried roots of P. tenuifolia revealed that saponins, xanthones, and oligosaccharides are the major and bioactive secondary metabolites [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies of the dried roots of P. tenuifolia revealed that saponins, xanthones, and oligosaccharides are the major and bioactive secondary metabolites [ 20 , 21 , 22 ]. Saponins are considered active ingredients of expectorants, antitussives, and short-term memory enhancers [ 19 , 23 ]. Xanthones exhibit anti-tumor [ 24 ], anti-inflammation [ 25 ], anti-thrombotic [ 26 ], and antimicrobial activities [ 27 ].…”
Section: Introductionmentioning
confidence: 99%